2009
DOI: 10.1111/j.1468-2982.2008.01836.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Cluster Headache in the Republic of Georgia: Results of a Population-Based Study and Methodological Considerations

Abstract: We present a study of the general-population prevalence of cluster headache in the Republic of Georgia and discuss the advantages and challenges of different methodological approaches. In a community-based survey, specially trained medical residents visited 500 adjacent households in the capital city, Tbilisi, and 300 households in the eastern rural area of Kakheti. They interviewed all (n = 1145) biologically unrelated adult occupants using a previously validated questionnaire. The household responses rates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 12 publications
2
18
0
1
Order By: Relevance
“…In Germany, suspected cluster headache cases detected by a questionnaire and interviewed by a neurologist in a population-based study revealed a prevalence of 0.12% [31]. In Georgia, one case was found in door-to-door survey among 1,145 individuals, which corresponds to 0.09% [32]. …”
Section: Resultsmentioning
confidence: 99%
“…In Germany, suspected cluster headache cases detected by a questionnaire and interviewed by a neurologist in a population-based study revealed a prevalence of 0.12% [31]. In Georgia, one case was found in door-to-door survey among 1,145 individuals, which corresponds to 0.09% [32]. …”
Section: Resultsmentioning
confidence: 99%
“…We can also compare with Georgia [18, 19], although the study here (the first supported by LTB) uniquely used a different questionnaire [33]. Like Lithuania, Georgia is a small European country, formerly part of the USSR, but it otherwise differs from Lithuania historically, ethnically and culturally.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, eastern Europe, and especially the countries of the former USSR, were very poorly represented among these [16, 17]. LTB addressed this with population-based studies in Georgia [18, 19] and Russia [20, 21], and Lithuania was included in the Eurolight Project [22]. …”
Section: Introductionmentioning
confidence: 99%
“…L'AVF est la plus fréquente des céphalées trigémino-autonomiques. [5]. Cette prévalence apparaît stable dans le temps et permet d'estimer qu'un sujet sur 1000 de la population générale serait porteur d'AVF (AP).…”
Section: Définitionunclassified